Bulked Segregant RNA-Seq Provides Distinctive Expression Profile Against Powdery Mildew in the Wheat Genotype YD588 - Ma, Pengtao; Wu, Liru; Xu, Yufei; Xu, Hongxing; Zhang, Xu; Wang, Wenrui; Liu, Cheng; Wang, Bo (Frontiers in Plant Science, 2021)
Wheat powdery mildew, caused by the fungal pathogen Blumeria graminis f. sp. tritici (Bgt), is a destructive disease leading to huge yield losses in production. Host resistance can greatly contribute to the control of this disease. To explore potential genes related to the powdery mildew (Pm) resistance, in this study, we used a resistant genotype YD588 to investigate the potential resistance components and profiled its expression in response to powdery mildew infection. Genetic analysis showed that a single dominant gene, tentatively designated PmYD588, conferred the powdery mildew resistance in YD588. Using bulked segregant RNA-Seq (BSR-Seq) and SNP association analysis, two high-confidence candidate regions were confirmed in chromosome arm 2B, spanning 453,752,054-506,356,791 and 584,117,809-664,221,850, respectively. To confirm the candidate region, molecular markers were developed by the BSR-Seq data and mapped PmYD588 to a 4.2 cM interval by the markers YTU588-004 and YTU588-008. The physical position was subsequently locked into the interval of 647.1-656.0 Mb, that was different from those of Pm6, Pm33, Pm51, Pm52, Pm63, Pm64, PmQ, PmKN0816, MlZec1 and MlAB10 on the same chromosome arm in its position, suggesting it is most likely a new Pm gene. To explore the potential regulatory genes of the R gene, 2,973 differentially expressed genes (DEGs) between the parents and bulks were analyzed through GO, COG and KEGG pathway enrichment analysis. According to these information, we selected 23 potential regulated genes in the enriched pathway of plant-pathogen interaction and detected their temporal expression patterns using an additional set of wheat samples and time-course analysis post-inoculation with Bgt. As a result, six disease-related genes showed distinctive expression profile after Bgt invasion and can served as key candidates for the dissection of resistance mechanism and improvement of durable resistance to wheat powdery mildew.